STUDIES ON NOVEL ENERGY AND NUTRIENTS SOURCE IN AFRICAN STAR APPLE (Chrysophyllum albidum) FOR FEEDING POULTRY. - Annongu, Azor Amos; Adebisi, Adeyina Oluwatoba; Eunice, Sola-ojo Foluke; Solomon, Ajide, Olusoji; Joseph, Kolade; Hugues, Edoh Jphannes (Journal of Agricultural Sciences (Belgrade), 2017)
Abstract Investigations on graded levels of virgin (untreated) Star Apple Seed Kernel Meal, SASKM initially analysed for nutrients and phytochemical composition, were conducted. SASKM was included in diets at different levels to replace maize as the major source of energy in monogastric poultry diet. Data on proximate composition including minerals, vitamins, amino acids and quantification of some of the seed anti-nutrients showed that the seed is high in nutrients especially carbohydrate as source of energy but contains high levels of anti-nutritional or toxic factors. Performance traits of broilers fed SASKM gave poor results (p<0.05) except the lack of mortality. Increment of dietary levels of the virgin SASKM did not however, negatively influence blood composition and most of the measured biochemical indices as the parameters were better than (p<0.05) or had the same values on the control diet as those on the test diets (p>0.05). Increasing levels of SASKM in diets caused elevation of AST, ALT, ALP and a significantly increment in blood urea levels among the raw seed meal based diets relative to the control diet (p<0.05). Based on performance, activities of enzymes and urea level data, it may be concluded that poultry could barely tolerate 5% raw SASKM in diets with minimum adverse effects. Subsequent research should process raw star apple seed meal before dietary inclusion for optimum results.